2000
DOI: 10.1002/etc.5620190812
|View full text |Cite
|
Sign up to set email alerts
|

Fate of 2,4,6‐trinitrotoluene in axenic sand culture systems containing smooth bromegrass

Abstract: Abstract-Plants have the potential to metabolize the munition 2,4,6-trinitrotoluene (TNT) in contaminated soils, sediments, and natural waters. However, microbial interference must be eliminated to demonstrate an intrinsic capacity for the metabolism of TNT by plants. An axenic sand culture system for smooth bromegrass (Bromus inermis Leyss) was established to investigate the influence of TNT on smooth bromegrass growth and metabolism. Shoot length growth was inhibited by 40% after 14 d of exposure to TNT at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…These activated carbon amendments maintained TNT concentration in soil solution below 5 mg/L. Corn root elongation measurements indicated tolerance of TNT at this concentration, which is consistent with reports for other terrestrial plants [13,23,24]. Our observations also confirmed the reported toxicity of TNT to microorganisms [8,17,18,20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These activated carbon amendments maintained TNT concentration in soil solution below 5 mg/L. Corn root elongation measurements indicated tolerance of TNT at this concentration, which is consistent with reports for other terrestrial plants [13,23,24]. Our observations also confirmed the reported toxicity of TNT to microorganisms [8,17,18,20].…”
Section: Discussionsupporting
confidence: 91%
“…We previously demonstrated accelerated TNT transformation and binding in the rhizosphere of corn plants because of increased activity of soil microorganisms and readily available carbon [22]. Some plants can effectively take up TNT and reduce it to amino derivatives [23], although transpiration and subsequent TNT uptake and transformation can decrease significantly at solution concentrations greater than 5 mg TNT/L [13]. The TNT similarly reduced the growth of other terrestrial plants at elevated concentrations [12,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if F. arundinacea did not influence the enrichment process, its roots would need to be permeable to alkane hydrocarbons but not nitrotoluenes. Typically, nitrotoluenes are readily absorbed by grasses, so this is probably not the case (30,31,45).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with plants have also demonstrated their ability to transform TNT to monoaminodinitrotoluenes and unidentified compounds more polar than TNT Sun et al, 2000;Thompson et al, 1998;Vanderford et al, 1997). Both emergent and submerged aquatic plants have been tested for their TNT tolerance and metabolism.…”
Section: Plant Metabolismmentioning
confidence: 99%
“…In another study TNT was transformed by the smooth bromegrass (Bromus inermis Leyss). However, a decrease in shoot length was observed, and the pretreatment of the plants with TNT decreased uptake and translocation of the radiolabel added in the form of [ 14 C-ring] TNT (Sun et al, 2000). Some recent research demonstrates the ability of plants to take up and covalently bind TNT metabolites (Bhadra et al, 1999c;Sens et al, 1999) and oxidatively transform TNT to 2-amino-4,6-dinitrobenzoic acid, 2,4-dinitro-6-hydroxy-benzyl alcohol, 2-N-acetoxyamino-4,6-dinitro-benzaldehyde, and 2,4-dinitro-6-hydroxytoluene (Bhadra et al, 1999a,b).…”
Section: Plant Metabolismmentioning
confidence: 99%